Aggregated chain morphological variation analysis of magnetorheological fluid (MRF) in squeeze mode. (10th September 2019) - Wang, Yongqing; Luo, Qi; Liu, Haibo; Wu, Jiakun; Lian, Meng; Li, Te
Abstract: Due to the synthetic effect of hydraulic force and magnetic force, chains in magnetorheological fluid (MRF) in squeeze mode appear bending even fracture, especially the latter of which has a potential influence on the macroscopic yield of MRF. Thus fracture mechanism of chains is investigated. As an important factor leading to fractrue, the magnetic force between particles is modelled. Based on the magnetic force model, a fracture criterion is established that when the horizontal component of magnetic force turns to zero, the fractrue phenomenon happens. Based on this criterion, fracture angle and fracture position of chains are analyzed. At last, fracture phenomenon was observed experimentally using an innovative device. It is found that the fracture was the result of interaction of hydraulic force and magnetic force. Driving effect of hydraulic force makes chains bend. Restoring effect of magnetic force prevents chains breaking up. When chains are bent to the extent that the fracture criterion is met, fracture phenomenon happens.